1998
DOI: 10.1111/j.1399-0039.1998.tb02993.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 promoter variants in patients with Graves' disease and Hashimoto's thyroiditis

Abstract: Graves' disease (GD) and Hashimoto's thyroiditis (HT) are T-cell mediated organ-specific autoimmune disorders with a genetic predisposition. The cytotoxic T-lymphocyte antigen 4 (CTLA-4) molecule is the predominant receptor for B7 on activated T cells and represents a negative regulator for T-cell function. Since the CTLA-4-guanine at position 49 of exon 1 is associated with susceptibility to GD as well as to HT and IDDM, we investigated a recently detected cytosine/thymine substitution at position -318 within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 11 publications
4
66
3
Order By: Relevance
“…The analysis of the CTLA-4 (AT) n polymorphism showed one common allele consisting of 8 AT repeats (AT) 8 and many uncommon alleles (frequency < 6%) ranging from (AT) 13 to (AT) 33 that we grouped as (AT) other . The (AT) 8 /(AT) other genotype was the most represented in both examined groups.…”
Section: Resultsmentioning
confidence: 93%
“…The analysis of the CTLA-4 (AT) n polymorphism showed one common allele consisting of 8 AT repeats (AT) 8 and many uncommon alleles (frequency < 6%) ranging from (AT) 13 to (AT) 33 that we grouped as (AT) other . The (AT) 8 /(AT) other genotype was the most represented in both examined groups.…”
Section: Resultsmentioning
confidence: 93%
“…Our results could explain the increased expression of CTLA-4 3 and the observed associations of the −318T allele to some diseases. 4 Homozygosity for −318/T in the promoter of Ctla-4 is rarely present in a Caucasian population. [4][5][6][7] In our previous study, the frequencies of individuals with genotypes −318C/C, C/T, and T/T were 86%, 17% and 0%, respectively, in healthy individuals (n = 122) and 69%, 31%, 0%, respectively, in patients with Wegener's granulomatosis (n = 32).…”
Section: Resultsmentioning
confidence: 99%
“…4 Homozygosity for −318/T in the promoter of Ctla-4 is rarely present in a Caucasian population. [4][5][6][7] In our previous study, the frequencies of individuals with genotypes −318C/C, C/T, and T/T were 86%, 17% and 0%, respectively, in healthy individuals (n = 122) and 69%, 31%, 0%, respectively, in patients with Wegener's granulomatosis (n = 32). When we considered the prevalence of longer (AT)n in the 3Ј-untranslated region together with the promoter single nucleotide polymorphism (SNP), we found that all patients carrying the −318T allele were homozygous for (AT)n Ͼ86 bp alleles.…”
Section: Resultsmentioning
confidence: 99%
“…23 The association of CTLA-4 and GD has also been confirmed in a family-based study using transmission disequilibrium test (TDT) analysis. 16 In contrast, association studies using a C/T SNP in the promotor of CTLA-4 at position -318 (C/T À318 ) were less consistent with some showing association 25 and others not. 24 CTLA-4 was also reported to be associated with HT in various populations including Caucasians 10,20 and Japanese, 13 although some studies did not find this.…”
Section: Introductionmentioning
confidence: 97%